Male and Female Pigeons (Columba livia-domestica) Behaviors in Matchmaking Period: Patterns and Interactions - Nugroho, Anwari Adi; Mardyah, Muthia; Saputra, Dian Andhi; Sarima, Sarima; Hidayad, Muhammad Nur (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
This study explores the social interaction behaviors of domestic pigeons (Columba livia domestica) during the matchmaking period. The aim is to understand how multi-channel communication through body movements, vocalizations, and tactile contact affects the formation of pair bonds. This research employed an observational method at the Green House of Universitas Veteran Bangun Nusantara using the ad libitum sampling technique to record daily behaviors of pigeons kept in a confined space. The results revealed that male pigeons predominantly initiate interactions, while females exhibit selective responses that determine mating success. Characteristic behaviors such as bowing, cooing, billing, and allopreening were observed to follow a sequential pattern from orientation and approach to attraction and acceptance. These findings suggest that the intensity and consistency of social interactions significantly contribute to successful pair bonding in domestic pigeons. Future research may investigate hormonal or neurological aspects that underlie these social behaviors.